Oral Administration of Transforming Growth Factor-β1 (TGF-β1) Protects the Immature Gut from Injury via Smad Protein-dependent Suppression of Epithelial Nuclear Factor κB (NF-κB) Signaling and Proinflammatory Cytokine Production - Shiou, Sheng-Ru (American Society for Biochemistry and Molecular Biology, 2013)
Inflammatory immune responses play an important role in mucosal homeostasis and gut diseases. Nuclear factor κB (NF-κB), central to the proinflammatory cascade, is activated in necrotizing enterocolitis (NEC), a devastating condition of intestinal injury with extensive inflammation in premature infants. TGF-β is a strong immune suppressor and a factor in breast milk, which has been shown to be protective against NEC. In an NEC animal model, oral administration of the isoform TGF-β1 activated the downstream effector Smad2 in intestine and significantly reduced NEC incidence. In addition, TGF-β1 suppressed NF-κB activation, maintained levels of the NF-κB inhibitor IκBα in the intestinal epithelium, and systemically decreased serum levels of IL-6 and IFN-γ. The immature human fetal intestinal epithelial cell line H4 was used as a reductionistic model of the immature enterocyte to investigate mechanism. TGF-β1 pretreatment inhibited the TNF-α-induced IκBα phosphorylation that targets the IκBα protein for degradation and inhibited NF-κB activation. Chromatin immunoprecipitation (ChIP) assays demonstrated decreased NF-κB binding to the promoters of IL-6, IL-8, and IκBα in response to TNF-α with TGF-β1 pretreatment. These TGF-β1 effects appear to be mediated through the canonical Smad pathway as silencing of the TGF-β central mediator Smad4 resulted in loss of the TGF-β1 effects. Thus, TGF-β1 is capable of eliciting anti-inflammatory effects by inhibiting NF-κB specifically in the intestinal epithelium as well as by decreasing systemic IL-6 and IFN-γ levels. Oral administration of TGF-β1 therefore can potentially be used to protect against gastrointestinal diseases.